NK Cells: A Double-Edged Sword in Chronic Hepatitis B Virus Infection - Maini, Mala K.; Peppa, Dimitra (Frontiers in Immunology, 2013)
There is natural enrichment of NK cells in the human liver and this intrahepatic predominance underscores their potential importance in the control of infections with hepatotropic viruses such as hepatitis B virus (HBV). The contribution of innate components during chronic HBV infection has been a relatively under-investigated area. However, recent data have highlighted that NK cells are capable of exerting antiviral and immunoregulatory functions whilst also contributing to the pathogenesis of liver injury via death receptor pathways. We will present an overview of current knowledge regarding the complex biology of NK cells in the context of their antiviral versus pathogenic role in chronic hepatitis B as a clinically relevant avenue for further investigation.